Peningkatan Hasil Belajar Materi Pembagian Melalui Model Think Pair Share Berbantu Media Jagung untuk Peserta Didik Kelas II SD N 1 Wonocoyo Tahun Ajaran 2017/2018 - Sri Rudati (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
This research is motivated by the low learning outcomes of mathematics in the division of class II material in SD Negeri I Wonocoyo. That was caused because the teacher had not used the right learning model so that the students did not understand the division material. To improve student learning outcomes, learning improvements are made through Classroom Action Research (CAR) which includes planning, action, observation and reflection with Think Pair Share learning models, namely 1) Thinking, 2) Pairing, and 3) Sharing (sharing). Data collection methods in this study use teacher and student observation sheets while data analysis uses quantitative and qualitative methods. This research was conducted through pre-cycle activities (before using the Think Pair Share model), cycle 1 and cycle 2 with the percentage of completeness in Pre-Cycle activities by 20% (3 students), in cycle I activities increased by 43% (6 students) to 64% (9 students). In cycle II there was a significant increase of 36% (5 students) so that in cycle II it was 100% complete (14 students).